Enhanced selective gas barrier properties of polystyrene via optimal reduced graphene oxide loading: balancing water vapor, oxygen resistance, and hydrogen permeability - Suyang Lu; Jie Su; Haoran Zhan; Jintai Li; Jiaqing Li; Xulin Yang; Zhoukun He; Xiaorong Lan; Wei Feng (Materials Research Express)
Polystyrene (PS), known for its low cost, excellent chemical stability, and optical transparency, has been widely used in various applications including electronic equipment, biomedicine, and food packaging. Although PS demonstrates some hydrogen permeability, its inherent oxygen and water vapor barrier properties require substantial improvement to meet advanced industrial standards. Reduced graphene oxide (rGO) has been extensively employed to enhance the oxygen and water vapor barrier performance of polymer materials. In this study, PS was selected to investigate the relationship between the optimal rGO loading and the oxygen/water vapor barrier properties as well as hydrogen permeability, aiming to achieve unique selective gas barrier characteristics. The water vapor transmission rate decreased significantly from 1.27 g/(m ^2 ·day) for pure PS to 0.48 g/(m ^2 ·day) for the 1% rGO-PS composite (1%GPS), demonstrating a remarkable improvement in water vapor barrier performance. Similarly, the incorporation of rGO nanofillers enhanced the oxygen barrier properties of PS, reducing the oxygen transmission rate from 4586.11 g/(m ^2 ·day) for pure PS to 138.32 g/(m ^2 ·day) for 1%GPS. Furthermore, the hydrogen transmission rates (HTR) of pure PS and 1%GPS were 907 cm ^2 /(m ^2 ·day·0.1 MPa) and 912 cm ^2 /(m ^2 ·day·0.1 MPa), respectively, indicating only a marginal increase in HTR. Consequently, the 1%GPS composite exhibits optimal barrier selectivity, combining superior water vapor barrier properties, oxygen barrier properties, and hydrogen permeability.